2016
DOI: 10.1016/j.neuropharm.2015.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Social isolation rearing increases dopamine uptake and psychostimulant potency in the striatum

Abstract: Social isolation rearing (SI) is a model of early life stress that results in neurobiological alterations leading to increased anxiety-like behaviors. These animals also exhibit an increased propensity to administer psychostimulants, such as cocaine; however, the mechanisms governing this increased addiction vulnerability remains to be elucidated. Long-term stressors have been shown to produce important alterations in nucleus accumbens core (NAc) function. The NAc regulates motivated and goal-directed behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
75
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 52 publications
9
75
0
Order By: Relevance
“…Extracellular levels of DA in the NAc are determined, in part, by DA transporter (DAT) activity (Ferris et al, 2014). The increased uptake of DA observed in the NAc core and shell of SI rats in the current study and in the NAc core in a previous report suggests that SI leads to augmented DAT levels in this brain region (Yorgason et al, 2015). Interestingly, other forms of chronic stress, such as repeated restraint stress, have also been shown to enhance DA uptake in the striatum (Copeland et al, 2005) and chronic ethanol exposure increases DA uptake in adult mouse, rat, and monkey models (Budygin et al, 2003;Karkhanis et al, 2015).…”
Section: Adolescent Si Disrupts Da Transmission In the Nacsupporting
confidence: 53%
“…Extracellular levels of DA in the NAc are determined, in part, by DA transporter (DAT) activity (Ferris et al, 2014). The increased uptake of DA observed in the NAc core and shell of SI rats in the current study and in the NAc core in a previous report suggests that SI leads to augmented DAT levels in this brain region (Yorgason et al, 2015). Interestingly, other forms of chronic stress, such as repeated restraint stress, have also been shown to enhance DA uptake in the striatum (Copeland et al, 2005) and chronic ethanol exposure increases DA uptake in adult mouse, rat, and monkey models (Budygin et al, 2003;Karkhanis et al, 2015).…”
Section: Adolescent Si Disrupts Da Transmission In the Nacsupporting
confidence: 53%
“…We have recently shown that blockade of dopaminergic neurotransmission by systemic administration of α-flupenthixol reduces motivation for social play in a lever pressing task, without altering the performance of social play during reinforced periods (Achterberg et al, 2016), although systemic treatment with higher doses of α-flupenthixol does reduce social play behavior . It has been shown that long periods of social isolation after weaning affect mesolimbic dopaminergic activity (Yorgason et al, 2013(Yorgason et al, , 2016Whitaker et al, 2013). Thus, in line with the view that NAc dopaminergic neurotransmission plays a critical role in incentive motivation (Barbano and Cador, 2007;Kelley, 2004;Salamone and Correa, 2012), we hypothesized that animals highly motivated for social play as a result of longer social isolation before testing would be more sensitive to blockade of NAc dopamine receptors.…”
Section: Discussionmentioning
confidence: 86%
“…These perturbations in accumbal dopamine release dynamics also persisted well into adulthood. Subsequent studies have now confirmed that aSI also leads to increased dopamine release and uptake in the dorsal striatum (Yorgason et al, 2016). This study also reported higher dopamine transporter levels in ventral and dorsal striatal tissue extracts from aSI rats, providing a possible mechanism that may contribute to the increased rate of dopamine uptake.…”
Section: Nucleus Accumbensmentioning
confidence: 88%